Outbreaks of foot-and-mouth disease in Burundi, East Africa, in 2016, caused by different serotypes - Estevez Garcia, A.I.; Lefebvre, D.J.; Nyabongo, Lionel; Haegeman, A.; Nkundwanayo, C.; Vleeschauwer, A. de; Ntakirutimana, D.; Leeuw, I. de; Nsanganiyumwami, D.; Niyokwizera, P.; Berg, T. van den; Niyokwishimira, A.; et al. (MDPI, 2022)
Burundi is a small, densely populated country in the African Great Lakes region. In March 2016, several hundreds of cattle were reported with vesicular lesions, suggesting foot-and-mouth disease (FMD). Epithelial samples, saliva, and blood were collected in six of the affected provinces spread over the country. The overall seroprevalence of FMD virus (FMDV) in the affected herds, as determined by antibodies against FMDV non-structural proteins, was estimated at 87%. Antibodies against FMDV serotypes O (52%), A (44%), C (19%), SAT1 (36%), SAT2 (58%), and SAT3 (23%) were detected across the provinces. FMDV genome was detected in samples from five of the six provinces using rRT-PCR. FMDV was isolated from samples from three provinces: in Cibitoke province, serotypes A and SAT2 were isolated, while in Mwaro and Rutana provinces, only serotype SAT2 was isolated. In Bururi and Cankuzo provinces, the serological profile suggested a recent incursion with serotype SAT2, while in Bubanza province, the serological profile suggested past incursions with serotype O and possibly serotype SAT1. The phylogenetic assessments showed the presence of topotypes A/Africa/G-I and SAT2/IV, similarly to previously characterized virus strains from other countries in the region, suggesting a transboundary origin and necessitating a regional approach for vaccination and control of FMD.